Gestión logística del transporte internacional de sustancias peligrosas (2022)
In this writing, it will be detailed how a good process is carried out for the international transport of dangerous goods, taking into account relevant aspects such as the labeling and labeling of goods and transport units, the responsibilities of each of the actors that involved, the respective documentation that must be provided in the process and a description of the vehicles that must be used. In addition, the transport of these goods presents a high volume of movement through roads from different countries, for this reason the proper handling that this activity should have is disclosed, based on this, the characteristics of each of these substances are identified, comparing their risks and imparting preventive knowledge to all workers and collaborators who participate in activities related to the handling of said substances. So, a series of regulations are created, created long ago by international organizations, which seek to prevent or mitigate accidents with this type of merchandise, and provide a series of labeling, packaging, storage and transportation provisions, that are complemented by the regulations of each country, in the particular case of Colombia some of them, Law 9 of 1979, Decree 1609 of 2002, NTC 1907, and NTC 4702 1-9.